IMPACT OF IMPLEMENTATION OF MBKM POLICY ON RESEARCH OF LECTURERS AND STUDENTS OF ABDURRAB UNIVERSITY - Siti Juariah,; Luluk Elvitaria,; Rosa Devitria,; Yulia Febrianita,; Sukri, (International Journal of Social Science, 2022)
Abdurrab University as one of the universities involved in the implementation of independent learning on an independent campus which progressively opens up opportunities for all study programs to implement this program. Some of them have been implemented by changing the curriculum that is relevant to MBKM learning, while some of them have substituted this research to find out the impact of implementing MBKM on the research activities of lecturers and students. The method used is a survey technique by measuring by distributing an open-ended questionnaire to respondents, namely lecturers and students at Abdurrab University. This research is part of a series of research that needs to be carried out regularly, considering the equality of implementation in each study program, faculty and university will be different every year. This research is expected to be a reference and evaluative guideline which can then be described in the form of policy recommendations. The results of the study stated that the implementation of MBKM had a significant impact on the research activities of lecturers and students.